Meningkatkan Kemampuan Siswa Dalam Berbahasa Inggris Dengan Menggunakan Lagu-lagu Berbahasa Inggris - Andi Mukarramah Nagauleng (LPPM IAIN Sorong, 2015)
This study is designed to improve the students’ reading comprehension ability through webbing strategy. It is conducted in order to find a strategy of teaching and learning that occurs, especially, in the teaching of reading skills. The strategy is selected because it is believed to be able to stimulate or activate the students to be more involved in the reading activities and to facilitate the students to comprehend the texts, especially expository texts. Thus, this study is directed to solve practical problems in the teaching and learning process. The research problem is formulated as follows: “How is the reading comprehension ability of the fourth semester students in school. Listening is one of the skills that are badly needed for everyone including those who are studying English. It is due to the fact that they spend much of their time in school listening. Besides, research demonstrate that people spend 60% of their time listening. Yet, students have not got good result yet in the subject of Listening Comprehension. This study is conducted to answer the research problem that is “Is there any effect of applying dictogloss on students’ Listening Comprehension achievement”? Thus, it is intended to obtain reliable information whether there is a significant difference in the students’ Listening Comprehension between the Experimental Group and the Control Group. This article describes about that